Towards the development of a medium-throughput assay to investigate the kinetics of β-Haematin formation in the presence of divers inhibitors - Fitzroy, Sharne-Mare (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.